A Framework for Designing Courses by Synergizing Project-Based Learning With Gamification - Muhammad Ishaq; Kamran Abid; Uzma Farooq; Kashif Ishaq; Nurhizam Safie; Adnan Abid (Human Behavior and Emerging Technologies)
The pedagogical methodologies have been influenced and improved with the help of many useful technological and other interventions. In the past, many efforts have been made to blend project-based learning (PBL) with gamification for a variety of domains. However, it is significant to construct a systematic framework of gamified project–based learning that can be used as a reference for designing and executing different courses in different educational settings. Hence, this research proposes a framework named MyGamify that comprises components including content domain, PBL, gamification, and a feedback system. This can be used as a reference framework for the instructors to design a course to be taught using PBL, augmented with gamification, for an improved learning experience. The framework has been formally validated by involving relevant experts, and it has been implemented with the help of an application that is exposed through web and mobile interfaces. Subsequently, to evaluate the effectiveness of the proposed framework, a longitudinal study has been conducted involving nearly 300 students and faculty members from two different institutions, whereby the course introduction to database systems has been redesigned accordingly and taught to the students of three different batches in the involved institutions using the following three different methods: (a) project at the end of the semester, (b) project throughout the semester, and (c) project throughout the semester blended with gamification. The data gathered by this study has been analyzed to identify the fulfillment of learning outcomes, students’ involvement, and percentage of project completion. The analysis reveals that the students performed well when combining PBL with gamification. It helped improve students’ involvement, better completion of projects, and better accomplishment of learning objectives by practicing the concepts throughout the semester on a well-defined project in a gamified environment.